(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In the current study, a sample of 40 soccer players elite and non-elite was chosen. There are 20 elite and 20 non-elite soccer players in the sample. Players of were chosen at random to serve as subjects. On average, elite and non-elite players ranged from 18 to 25. Data will be gathered using a tools like skinfold calliper, bone calliper weigh machine, measuring tape. It also demonstrates that there is a substantial difference between elite and non-elite soccer players with elite players displaying a marginally greater anthropometric profile than non- elite players. Consequently, there is a considerable difference in endomorphic, mesomorphic and ectomorphic in elite and non-elite soccer players. The elite players have slightly better profile then non-elite soccer players. The difference occurs might be the reason is the elite players are training on the regular basis and the non-elite are irregular in there training.